Rapid gas–liquid reaction in flow. Continuous synthesis and production of cyclohexene oxide - Mandai, Kyoko; Yamamoto, Tetsuya; Mandai, Hiroki; Nagaki, Aiichiro (Beilstein Journal of Organic Chemistry, 2022)
The enhanced reaction rate in the epoxidation of cyclohexene with air as an oxidant was discovered without any added catalyst utilizing a continuous flow reactor constructed with readily available stainless steel parts and devices. This continuous-flow process demonstrates a significant improvement in reaction time for highly selective epoxide production over the batch process due to the efficient mass transfer between the liquid phase and air. The flow process discovered was operated continuously with good operational stability, evaluated by a constant high yield of cyclohexene oxide, to obtain the desired product with high productivity.
Keywords: air; continuous flow; cyclohexene oxide; flow epoxidation; rapid gas–liquid reaction

(untitled) - Fujita, H.; Yoshimatsu, H.; Miki, C.; Shirai, T.; Hata, T.; Sakamoto, M. (Chem. Lett., 2021)

(untitled) - Oral, A.; Tasdelen, M. A.; Demirel, A. L.; Yagci, Y. (J. Polym. Sci., Part A: Polym. Chem., 2009)

(untitled) - Chang, H.; Li, D.; Cao, T.; Li, Q.; Bu, Z.; Zhao, W.; Lin, T. (Polym. Adv. Technol., 2018)

(untitled) - Koning, C.; Wildeson, J.; Parton, R.; Plum, B.; Steeman, P.; Darensbourg, D. J. (Polymer, 2001)

(untitled) - Muthuraj, R.; Mekonnen, T. (Polymer, 2018)

(untitled) - Trost, B. M. (Org. Process Res. Dev., 2012)

Selective Oxidation by Heterogeneous Catalysis - Centi, G.; Cavani, F.; Trifirò, F. (Trends and Outlook in Selective Oxidation, 2001)

Modern Oxidation Methods - Adolfsson, H. (Transition Metal‐Catalyzed Epoxidation of Alkenes, 2004)

(untitled) - Yamada, T.; Takai, T.; Rhode, O.; Mukaiyama, T. (Bull. Chem. Soc. Jpn., 1991)

(untitled) - Kaneda, K.; Haruna, S.; Imanaka, T.; Hamamoto, M.; Nishiyama, Y.; Ishii, Y. (Tetrahedron Lett., 1992)

(untitled) - Ikawa, T.; Fukushima, T.; Muto, M.; Yanagihara, T. (Can. J. Chem., 1966)

(untitled) - Serra, A. C.; Rocha Gonsalves, A. M. d'A. (Tetrahedron Lett., 2011)

(untitled) - Lesieur, M.; Battilocchio, C.; Labes, R.; Jacq, J.; Genicot, C.; Ley, S. V.; Pasau, P. (Chem. – Eur. J., 2019)

(untitled) - Ahlqvist, G. P.; Burke, E. G.; Johnson, J. A.; Jamison, T. F. (Polym. Chem., 2021)

(untitled) - Gambacorta, G.; Sharley, J. S.; Baxendale, I. R. (Beilstein J. Org. Chem., 2021)

Liquid Phase Aerobic Oxidation Catalysis: Industrial Applications and Academic Perspectives - Gemoets, H. P. L.; Hessel, V.; Noël, T. (Reactor Concepts for Aerobic Liquid phase Oxidation: Microreactors and Tube Reactors, 2016)

(untitled) - Kasakado, T.; Fukuyama, T.; Nakagawa, T.; Taguchi, S.; Ryu, I. (Beilstein J. Org. Chem., 2022)

(untitled) - Saito, Y.; Nishizawa, K.; Laroche, B.; Ishitani, H.; Kobayashi, S. (Angew. Chem., Int. Ed., 2022)

(untitled) - Takumi, M.; Sakaue, H.; Nagaki, A. (Angew. Chem., Int. Ed., 2022)

(untitled) - Ashikari, Y.; Tamaki, T.; Takahashi, Y.; Yao, Y.; Atobe, M.; Nagaki, A. (Front. Chem. Eng., 2022)

(untitled) - Ashikari, Y.; Maekawa, K.; Ishibashi, M.; Fujita, C.; Shiosaki, K.; Bai, H.; Matsuyama, K.; Nagaki, A. (Green Process. Synth., 2021)

(untitled) - Ashikari, Y.; Tamaki, T.; Kawaguchi, T.; Furusawa, M.; Yonekura, Y.; Ishikawa, S.; Takahashi, Y.; Aizawa, Y.; Nagaki, A. (Chem. – Eur. J., 2021)

(untitled) - Tamaki, T.; Nagaki, A. (Tetrahedron Lett., 2021)

(untitled) - Mallia, C. J.; Baxendale, I. R. (Org. Process Res. Dev., 2016)

(untitled) - Yamamoto, T.; Tonomura, O.; Nagaki, A. (J. Chem. Eng. Jpn., 2020)

(untitled) - Vanoye, L.; Wang, J.; Pablos, M.; de Bellefon, C.; Favre-Réguillon, A. (Catal. Sci. Technol., 2016)

(untitled) - Zhou, Y.; He, W.; Fang, Z.; Guo, K. (ChemistrySelect, 2018)

(untitled) - Hone, C. A.; Kappe, C. O. (Top. Curr. Chem., 2019)

(untitled) - Gérardy, R.; Emmanuel, N.; Toupy, T.; Kassin, V.-E.; Tshibalonza, N. N.; Schmitz, M.; Monbaliu, J.-C. M. (Eur. J. Org. Chem., 2018)

(untitled) - Hone, c. A.; Roberge, d. M.; Kappe, C. O. (ChemSusChem, 2017)

(untitled) - Wentzel, B. B.; Alsters, P. L.; Feiters, M. C.; Nolte, R. J. M. (J. Org. Chem., 2004)

(untitled) - Yahiaoui, A.; Belbachir, M.; Soutif, J. C.; Fontaine, L. (Mater. Lett., 2005)